2005
DOI: 10.1074/jbc.m504244200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Requirement for Phospholipase D/Spo14 and Its Novel Interactor Sma1 for Regulation of Exocytotic Vesicle Fusion in Yeast Meiosis

Abstract: During sporulation and meiosis of budding yeast a developmental program determines the formation of the new plasma membranes of the spores. This process of prospore membrane (PSM) formation leads to the formation of meiotic daughter cells, the spores, within the lumen of the mother cell. It is initiated at the spindle pole bodies during meiosis II. Spore formation, but not meiotic cell cycle progression, requires the function of phospholipase D (PLD/Spo14). Here we show that PLD/Spo14 forms a complex with Sma1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 38 publications
4
28
2
Order By: Relevance
“…Of the 45 mutants, eight met these criteria: erv14⌬, gcs1⌬, mso1⌬, rcy1⌬, sma1⌬, sma2⌬, sec22⌬ and vps13⌬ (Table 1). Of these mutants, three, MSO1, SMA1 and GCS1, have recently been reported to have prospore membrane defects Riedel et al, 2005;Connolly and Engebrecht, 2006), validating our screen. The remaining mutants affecting prospore membrane growth were characterized further.…”
Section: Screening For Prospore Membrane Formation Mutantssupporting
confidence: 51%
“…Of the 45 mutants, eight met these criteria: erv14⌬, gcs1⌬, mso1⌬, rcy1⌬, sma1⌬, sma2⌬, sec22⌬ and vps13⌬ (Table 1). Of these mutants, three, MSO1, SMA1 and GCS1, have recently been reported to have prospore membrane defects Riedel et al, 2005;Connolly and Engebrecht, 2006), validating our screen. The remaining mutants affecting prospore membrane growth were characterized further.…”
Section: Screening For Prospore Membrane Formation Mutantssupporting
confidence: 51%
“…Thus, the catalytic activity of Spo14p appears to be necessary for additional aspects of membrane growth. A recent, independent study of Spo14p and its sporulation-specific binding partner Sma1p reported the same accumulation of SPB-associated vesicles in spo14 cells that we describe here (Riedel et al, 2005). Mutation of SMA1, however, resulted in formation of a membrane cap on the SPB, but a failure in continued expansion of the prospore membrane.…”
Section: Discussionmentioning
confidence: 40%
“…The phenotype of a spo14 null mutant is similar to that of the sso1 and sec9 spo20 mutants, indicating that Spo14 also participates in vesicle fusion (Riedel et al 2005;Nakanishi et al 2006). Studies of nonnull alleles of SPO14 and of mutations affecting the Spo14-interacting protein, Sma1, indicate that Spo14 acts at two discrete steps in PSM formation: the initial fusion of vesicles on the meiotic plaque and subsequent enlargement of the PSM to surround the adjoining nucleus (Riedel et al 2005;Nakanishi et al 2006).…”
mentioning
confidence: 78%
“…Since these proteins are involved in vesicle fusion during PSM formation (Riedel et al 2005;Nakanishi et al 2006), it is likely that Ssp2 also plays a role in vesicle fusion. As noted in the Introduction, Spo14 in both initiation and expansion of the PSM (Riedel et al 2005;Nakanishi et al 2006). Similarly, Ssp2 could act at both steps.…”
Section: Resultsmentioning
confidence: 99%